Dealing with security issues in IoT - Radhika Sreedharan (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2023)
IoT (Internet of Things) is related to design of a lot of inter-related “contrived" gadgets having finite capacities with regard to memory and processing power and design is like an Internet. These are frequently battery-driven, raises requirement for adopting environment-friendly techniques. Between the noteworthy ultimatum that establishing interrelated smart objects accompanies are uniformity and coordination. Many smart objects are presumed to develop and addresses of IPv4 are normally utilized. IPv6 is recognized as a possibility for smartobject transmission. Internet of Things (IoT) is a global network of physical and virtual ‘things’ connected to the internet. All objects have unique IDs that are utilized for identification. IoT is the emerging technology which can change the way we communicate with devices. Hereafter almost every electronic device will be a smart device that will be able to compute and communicate with handheld and other infrastructure gadgets. The Internet of Things utilization builds a lot of security problems, which arises from • Smart objects essence: utilization of cryptographic algorithms which are delicate, with regard to requirements of processing and memory. • Quality protocols utilization and the requirement to reduce the data quantity swapped among nodes. An IoT usage which accumulates or handles consumer distinctive data like bank particulars require a foremost rank of security, while a sensor linked to a station area will have a low rank. It need not be costly to carry out fundamental security steps; but it is significant to determine a security strategy and incorporate recuperation measures in the security problems incidents. The main aim of this topic is to describe mechanisms which can help to deal with IoT security issues.